2022
DOI: 10.1155/2022/9880827
|View full text |Cite
|
Sign up to set email alerts
|

Acute Generalized Exanthematous Pustulosis following SARS-CoV-2 Virus: Remdesivir as a Suspected Culprit

Abstract: Acute generalized exanthematous pustulosis (AGEP) is an exanthematous condition, predominantly occurring as a result of drug reactions. We, hereby, present the first case of AGEP following treatment with remdesivir in a patient with COVID-19, without hydroxychloroquine use, which serves as a reminder to consider remdesivir as a possible causative agent when dealing with AGEP presentation in COVID patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Similar to our study, Mohaghegh et al presented the first reported case of AGEP following treatment with remdesivir 2 days after the completion of treatment in a patient with COVID‐19 1 . Alzahrani et al, reported a case of AGEP in a 34‐year‐old male that presented with pustular rash on erythematous base 4 days after his COVID‐19 was resolved.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our study, Mohaghegh et al presented the first reported case of AGEP following treatment with remdesivir 2 days after the completion of treatment in a patient with COVID‐19 1 . Alzahrani et al, reported a case of AGEP in a 34‐year‐old male that presented with pustular rash on erythematous base 4 days after his COVID‐19 was resolved.…”
Section: Discussionsupporting
confidence: 88%
“…In the COVID‐19 era, cases of acute generalized exanthematous pustulosis (AGEP) after COVID‐19 infection and the use of COVID‐19 medications such as hydroxychloroquine (HCQ) and cefepime have been reported 1–3 . Herein, we report a challenging case that presented with AGEP following COVID‐19 infection and a history of remdesivir use.…”
Section: Introductionmentioning
confidence: 98%
“… 6 Interestingly, an increasing incidence of AGEP has been reported since the start of the COVID-19 pandemic, suspected to be a result of the pathogen itself or the new combination of medications introduced for treatment. 7 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the coronavirus disease 2019 (COVID‐19) has given rise to several new‐onset or exacerbated dermatologic disorders 4 . Moreover, medications used in the settings of SARS‐CoV‐2 infection, as well as various types of COVID vaccine, have also been followed by cutaneous adverse events 5,6 . The incidence and prevalence of vitiligo have increased considerably since the beginning of the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, medications used in the settings of SARS-CoV-2 infection, as well as various types of COVID vaccine, have also been followed by cutaneous adverse events. 5,6 The incidence and prevalence of vitiligo have increased considerably since the beginning of the COVID-19 pandemic. The reason could be the viral infection itself, medications used for the treatment, and vaccines introduced to prevent the disease as well as psychologic distress of pandemics.…”
mentioning
confidence: 99%